PERMUKIMAN TERAPUNG DANAU TEMPE DI KABUPATEN SOPPENG PROVINSI SULAWESI SELATAN - , Ahsan Laode ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Floating Settlement of Lake Tempe is a unique form of settlement. The annual cycle of tidal water of the lake does not only affect people's livelihoods, but also affects the position of the settlements. At high tide, the residents work as fishermen, and at low tide in the dry season the resident work as farmer in the land of the former lake. The settlement position when the high tide is on the edge of the lake close to the mainland, while at low tide the settlements position moves to the middle of the lake or areas where water still flooded . Lake Tempe is located in the central part of South Sulawesi Province which covers three districts, they are District of Wajo, Sidrap and Soppeng. This research was conducted in District of Soppeng, precisely Limpomajang Village, Sub-district Marioriawa. This research aims to explore the concept of floating settlements of Lake Tempe on District of Soppeng, Province of South Sulawesi. This research is a qualitative descriptive with phenomenology approach. Data analysis using inductive analysis, and determination respondents is combine purposive and snowball sampling . Residents who living in floating settlements of Lake Tempe were fishermen who used to live on the mainland. The potential large fishing of the lake becoming a major attraction for fishermen to live in the lake. They want to be closer to where they fish so they can save time, labor and fuel costs. Some of them live in the lake because they have no land to make a home on the mainland. For some people living in the floating settlements is their primary residence, but for some others just make a floating house as a place to rest or store fishing equipment because they are still have a house on the mainland. All activities carried out over the water daily. There are no public facilities such as education, health, market and mosque in floating house. To meet the needs for the resident should rise to the mainland. The main source of water for bathing and washing is lake water, while for drinking water taken from water sources that exist in the mainland. This research found that the concept of settlement in Tempe Lake is the concept of settlement with lake nature and fishing based wich formed by four main themes, namely: 1) Local knowledge in the context of adaptation to the natural environment of the lake, 2) Local knowledge of the implications of the determination palawang